The Conditional Heteroscedasticity of the Yen-Dollar Exchange Rates - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1998)
This paper examines the conditional heteroscedasticity of the yen-dollar exchange rate. A model is constructed by extending the asymmetric power autoregressive conditional heteroscedasticity model to a process that is fractionally integrated. It is found that, unlike the equity markets, the appreciation and depreciation shocks of the yen against the dollar have similar effects on future volatilities. Although the results reject both the stable and the integrated models, our analysis of the response coefficients of the past shocks and the application of the models to the estimation of the capital requirements for trading the currencies show that there are no substantial differences between the fractionally integrated models and the stable models.